West African Economic and Monetary Union (WAEMU) : Recent Economic Developments and Regional Policy Issues in 2000. (IMF Staff Country Reports; Country Report ;, 2001)
There has been a marked deterioration in the economic and financial performance of the West African Economic and Monetary Union (WAEMU) as a whole. These developments reflected unfavorable terms of trade, political conflicts in certain countries, and a weakening of adjustment policies. Progress needs to be made in achieving fiscal consolidation and macroeconomic convergence among WAEMU member countries. It would be important to achieve a greater integration of the WAEMU region's money and financial markets.